A comparative study of various current mirror configurations: Topologies and characteristics. (July 2016) - Aggarwal, Bhawna; Gupta, Maneesha; Gupta, A.K.
Abstract: Current mirror is a fundamental unit, widely used for current amplification, biasing and active load in various analog/mixed mode integrated circuits. Its efficient design plays a major role in deciding the overall performance of these circuits. In literature, various techniques have been developed and proposed to improve the performance parameters of a current mirror like accuracy, input resistance, output resistance and bandwidth etc. This paper is an effort to bring all these techniques on a single platform and compare their advantages and disadvantages. Here, a detailed survey of various current mirror topologies has been carried out and these topologies have been categorized on the basis of various characteristic parameters. The discussed circuits have been simulated using Mentor Graphics Eldo spice in TSMC 0.18 µm CMOS, BSIM3 and Level 53 technology. In order to get a fair comparison among these techniques, simulations under similar conditions using a supply voltage of 1.8 V have been performed.